The Role of Media Convergence in the Netflix App in Generation Z’s Daily Life - Daffa Lintang Gautama; Yasser Fikry (Communigate, 2025)
Media convergence is an inevitable occurrence for mass media companies because convergence is the key to the sustainability of the media industry in the current multimedia era. Media convergence also cannot be separated from student life, therefore media convergence on the Netflix application is one of their new choices in order to meet the satisfaction of entertainment. The purpose of this study is to identify the role of media convergence in the Netflix application in the daily lives of Gen Z, and this study uses qualitative methods which later researchers will collect data by conducting interviews with 2 Gen Z who watch shows on Netflix and 1 expert informant who is experienced in the field of video streaming. After the interview is conducted, the data will be transcribed and reanalyzed by coding. The results of this study show that the media convergence that occurs on Netflix has its own role for Gen Z, they now prefer to watch movies or series through Netflix because they can be watched anywhere and anytime, Netflix is also indirectly a source of information for Gen Z, although they still have the purpose of watching shows on Netflix as entertainment. Basically, the internet is the main factor why media convergence on Netflix and other video streaming applications occurs, because the internet can change the style and way of life of humans to all aspects of life.